GARS‐related disease in infantile spinal muscular atrophy: Implications for diagnosis and treatment. Issue 5 (17th March 2020) - Markovitz, Rebecca; Ghosh, Rajarshi; Kuo, Molly E.; Hong, William; Lim, Jaehyung; Bernes, Saunder; Manberg, Stephanie; Crosby, Kathleen; Tanpaiboon, Pranoot; Bharucha‐Goebel, Diana; Bonnemann, Carsten; Mohila, Carrie A.; et al.
Abstract: The majority of patients with spinal muscular atrophy (SMA) identified to date harbor a biallelic exonic deletion of SMN1 . However, there have been reports of SMA‐like disorders that are independent of SMN1, including those due to pathogenic variants in the glycyl‐tRNA synthetase gene ( GARS1 ) . We report three unrelated patients with de novo variants in GARS1 that are associated with infantile‐onset SMA (iSMA). Patients were ascertained during inpatient hospital evaluations for complications of neuropathy. Evaluations were completed as indicated for clinical care and management and informed consent for publication was obtained. One newly identified, disease‐associated GARS1 variant, identified in two out of three patients, was analyzed by functional studies in yeast complementation assays. Genomic analyses by exome and/or gene panel and SMN1 copy number analysis of three patients identified two previously undescribed de novo missense variants in GARS1 and excluded SMN1 as the causative gene. Functional studies in yeast revealed that one of the de novo GARS1 variants results in a loss‐of‐function effect, consistent with other pathogenic GARS1 alleles. In sum, the patients' clinical presentation, assessments of previously identified GARS1 variants and functional assays in yeast suggest that the GARS1 variants described here cause iSMA. GARS1 variants have been previously associated with Charcot–Marie–Tooth disease (CMT2D) and distal SMA type V (dSMAV). Our findings expand the allelic heterogeneity of GARS ‐associated disease and support that severe early‐onset SMA can be caused by variants in this gene. Distinguishing the SMA phenotype caused by SMN1 variants from that due to pathogenic variants in other genes such as GARS1 significantly alters approaches to treatment.